Essays on regional economic development: finance, growth, and income distribution - Petach, Luke, author; Pena, Anita Alves, advisor; Tavani, Daniele, advisor; Weiler, Stephan, committee member; Opp, Susan, committee member (Colorado State University. Libraries, 2019)
This dissertation explores the relationship between financial markets and economic activity across regions within the United States. In particular, it examines how regional variation in financial markets may affect variables that play an important role in regional economic growth and income distribution. Despite the way the Great Recession of 2007-2009 made manifest the importance of financial markets in the determination of real economic outcomes, there is still much that is not understood about the relationship between financial markets and the rest of the economy. Financial markets may affect household decision making either indirectly via their influence over institutional arrangements and social norms, or directly via their influence over who can obtain access to the credit needed to start a business, purchase a home, or invest in human capital. These changes will alter the distribution of income—both directly via the re-distribution of funds through credit markets, and indirectly via the outcomes that access to credit (or lack there-of) engender.
Keywords: debt; growth and distribution; regional economics; financialization; banking; political economy